Peran Kepala Sekolah dalam Peningkatan Mutu Pendidikan Agama Islam Melalui Manajemen Berbasis Sekolah - Dina Mardiana; Zulfikar Yusuf (Lembaga Penelitian, Penerbitan dan Pengabdian (LP3M) IAI Al-Urwatul Wutsqo Jombang, 2019)
Based on observations and documentation, it is found that in SMP Muhammadiyah 4 Singosari Malang in the last three years the number of students has decreased. From 2016 with a number of students totaling 180 people, decreased in 2017 to 160 people and in 2018 to 150 students. This phenomenon is the focus of the problem so this research aims to analyze the role of the headmaster of the Muhammadiyah 4 Junior High School in Singosari Malang in improving the quality of education through school-based management. This research uses a qualitative approach to the type of case study. Muhammadiyah 4 Junior High School Singosari was used as the object of research. The results of the study stated that: 1) The headmaster of Muhammadiyah 4 Junior High School had performed the managerial task well. The planning aspect is done by placing the human resources of educators according to their competencies. In the aspect of implementation and supervision the school principal is fully responsible. In the aspect of administration evaluation done well, but in the aspect of indicators, it has not been clearly determined in each semester / year. 2) There are two obstacles experienced by school principals, namely non-permanent human resources in schools and infrastructure facilities especially the PAI laboratory for the means of knowledge and development of PAI in schools.